Demonstrationsmodell av elektrisk motor styrd av motriktad elektromotorisk kraft Med test av magnetiska lager - Åkesson, Joakim; Öhrnberg, Fabian (My University, 2014)
Reduced material consumption is a contributing factor when reducing environmental impact. Reusing current resources can save energy as well. Furthermore these two aspects can be linked to how BLDC machines are designed and operated. Normally they are operated with Hall sensors to detect the rotor position, which is necessary for the transistors to commutate at a correct point. However, there is another method for detecting the rotor position. When an electric motor is operating, it also generates voltage, so-called back electromotive force (back-EMF), which can be used as signal for detection the rotor position. BLDC motors are normally operated with three-phase inverter bridges. By adjusting the commutation of the transistors in the inverter bridge so that it matches the phase of the back-EMF, hall sensors may be completely excluded. This can cause a reduction in material consumption during production and thus also reduce impact on the environment. In addition to using less material, control can also be streamlined further due to measuring directly on the stator windings. For further attempt to improve efficiency and reduce environmental impact this project has experimented with magnetic bearings. This was made successful with an exception for the magnetic bearings. Consequently a self-designed engine could be controlled by back-EMF as a feedback mechanism. The engine managed lighter load, but there are however still areas which can be developed further. An example of a development point is to create a more flexible control which can automatically adjust itself to the connected motor.
Keywords: Data- och informationsvetenskap; Computer and Information Science